Sophine's World : A Novel About the History of Philosophy - Gaardeer, Jostein (London Phoenix, 1996)
The protagonists are Sophie Amundsen, a 14-year-old girl, and Alberto Knox, her philosophy teacher. The novel chronicles their metaphysical relationship as they study Western philosophy from its beginnings to the present. A bestseller in Norway.
Include Index
Keywords: Philosophy -- Teenage girls -- Norway